Dealing with Climate Change: Paleoclimate research in Australia - Meissner, K.; Abram, N.; Armand, L.; Chase, Z.; De Deckker, P.; Ellwood, M.; Exon, N.; Gagan, M.; Goodwin, I.; Howard, W.; Lough, J.; McCulloch, M.; et al. (Australasian Quarternary Association, Inc., 2015)
Palaeoclimate research relevant to marine systems in Australia includes the collection and analysis of: (a) shallow-water and deep-sea corals, which provide highresolution archives, (b) deep-sea sediment and ice cores, which span longer time scales, and (c) palaeoclimate modelling, which gives us insights into mechanisms, dynamics and thresholds underlying past climate states. Palaeoclimate research in Australia is mature and well recognised internationally. To further advance Australian palaeoclimate research, we must address major challenges that include insufficient research vessel access, insufficient targeted research funding, as well as the lack of a well funded national centre to coordinate research efforts (e.g. academic institution or ARC Centre of Excellence for Palaeoclimate Research).